Wireless Power Transfer Empowered by Reconfigurable Intelligent Surfaces - Wang, Hsuan-Fu; Ueng, Fang-Biau; Tsai, Feng-Cheng (IEEE Global Conference on Consumer Electronics, 2023)
Reconfigurable intelligent surfaces (RIS) are considered as a promising revolutionary hardware technology that can improve the energy and spectral efficiency of wireless networks. RIS is composed of programmable metasurface and can efficiently control the wavefront (phase, amplitude, frequency, and even polarization) of incident signals without complex signal processing. With the support of RIS, the network can control the radio waves, thereby overcoming the negative effects of natural wireless propagation. The focus of this paper is the study of a multi-user multiple-input multiple-output (MIMO) wireless power transfer (WPT) system assisted by multiple RISs, where the transmitter is equipped with a constant-envelope analog beamformer. First, we maximize the user's total received power by jointly optimizing the phase shift of the RIS and the beamformer of the transmitter, and propose an alternating optimization-based solution by exploiting semidefinite relaxation (SDR). However, considering user fairness, we formulate another problem to maximize the total received power subject to the user's individual minimum received power constraint. To solve this problem, we propose an iterative algorithm based on Alternating Direction Multiplier Method (ADMM).